Pengaruh Anemia Dalam Kehamilan Terhadap Kejadian Ketuban Pecah Dini - Ari Antini; Irna Trisnawati (MEDIA ILMU KESEHATAN, 2026)
Background: Incidence PROM in Indonesia ranges 4.5%-6% of all pregnancies, while abroad between 6%-12%. According to RSUD Karawang in 2021, PROM ranked 2nd at 35.4%. One of the maternal deaths with PROM caused by anemia. Anemia is one of the predisposing factors PROM. Incidence pregnancy anemia in Indonesia 12-70%. The prevalence of anemia among pregnant women in Karawang Regency in 2023 was 43.75%, far exceeding the WHO standard of <20%. Objective: to determine the effect anemia during pregnancy with PROM at RSUD Karawang. Methods: cross-sectional design. Univariate, bivariate, and multivariate analyses were conducted using multiple logistic regression. The study population and sample consisted 120 pregnant women at RSUD Karawang in 2024. The sampling technique used accidental sampling.Results: incidencef PROM at RSUD Karawang was 19.2%. The p-value 0.453 (>0.005), indicating no significant association anemia and PROM. This was possible because the data collection period was limited, resulting in only 6% of the surveyed mothers with KPD being found to have anemia. The results multivariate analysis smoking behavior significantly associated with incidence PROM controlling for anemia with p-value of 0.047.Conclusion: There was no significant association anemia and the incidence PROM at RSUD Karawang